2019
DOI: 10.1111/jcpp.13123
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic neural circuitry of depression in adolescent females

Abstract: Background Adolescence is characterized by affective and cognitive changes that increase vulnerability to depression, especially in females. Neurodevelopmental models attribute adolescent depression to abnormal responses in amygdala, striatum, and prefrontal cortex (PFC). We examined whether the strength of functional brain networks involving these regions predicts depression symptoms in adolescent females. Methods In this longitudinal study, we recorded resting‐state functional connectivity (RSFC) in 174 adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The first rs-fMRI longitudinal study in adolescent MDD was published in 2011. 62 Low- and middle-income countries (LMIC) were underrepresented, with only one study from Brazil 60 as compared to eight from the United States 58 , 62 , 63 , 65 , 66 - 69 , 71 and four from Australia. 61 , 64 , 67 , 70 Sample sizes ranged from 41 to 637 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first rs-fMRI longitudinal study in adolescent MDD was published in 2011. 62 Low- and middle-income countries (LMIC) were underrepresented, with only one study from Brazil 60 as compared to eight from the United States 58 , 62 , 63 , 65 , 66 - 69 , 71 and four from Australia. 61 , 64 , 67 , 70 Sample sizes ranged from 41 to 637 subjects.…”
Section: Resultsmentioning
confidence: 99%
“… 60 , 65 Smaller samples reported on well-characterized clinical MDD, 63 - 65 , 69 whereas larger studies were frequently drawn from community-based samples in which categorical MDD assessment was not commonly performed. 58 , 61 , 62 , 66 - 68 , 70 , 71 Some of these community-based studies only reported dimensional measures of depressive symptoms from specific (Child Depression Inventory, Center for Epidemiological Studies Depression scale) or non-specific (Youth Self-Report and Adult Self-Report, Child and Adolescent PsychProfiler) instruments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression may be related to impaired FC of some other networks, e.g., sensorimotor [ 30 33 ], ventral and dorsal attention [ 32 33 ], language [ 25 ], affective [ 11 , 17 , 31 ], visual [ 23 , 33 ], and audial [ 23 , 33 ]. Some researchers also proposed spatial brain patterns that they view as networks of depression [ 34 36 ] or its certain features like rumination [ 37 ] or social emotion disruption [ 5 ].…”
Section: Introductionmentioning
confidence: 99%